Genjek Bali Audiobook Based on the Pancasila Student Profile to Enhance Genjek Singing Skills of Visually Impaired Children - Putu Listya Candra Dewi; I Gusti Agung Ayu Wulandari; I Made Citra Wibawa (International Journal of Elementary Education, 2025)
Music art learning for blind children is still often done monotonously without appropriate media variations, so it is less able to improve learning outcomes and active student participation. The lack of contextual and adaptive learning media for the needs of the blind encourages the need to develop innovative media such as genjek audiobooks based on the Pancasila Student Profile. This study aims to develop a traditional singing learning medium called genjek in music education for visually impaired children. This research is a development study by adapting the ADDIE development model. The test subjects in this study included one material expert, one design expert, one media expert, and 12 visually impaired children. Data collection was conducted using non-test methods such as questionnaires and performance assessment sheets. This study employed four data analysis techniques, namely qualitative descriptive analysis, quantitative descriptive analysis, descriptive statistical analysis, and inferential statistical analysis (t-test). The results of the study showed that the eligibility based on the evaluations of content experts, design experts, media experts, individual trials, and small group trials, scored 92.25%, 95%, 96%, 93.2%, and 92.5% respectively all categorized as very good. The effectiveness test based on a one-sample t-test yielded a t-value of 3.046. Meanwhile, the ttable value at a 5% significance level with 11 degrees of freedom was 1.796. These results indicate that tvalue > ttable, leading to the rejection of H0 and acceptance of H1. It can be concluded that the genjek Bali audiobook medium based on the Pancasila Student Profile is highly feasible and effective for use to enhance the learning outcomes of visually impaired children while also implementing character values within the dimensions of the Pancasila Student Profile. Implicating this research, the audiobook genjek media effectively enhances learning outcomes and instills character values in visually impaired children in music education.